Enhancing employee performance in medium manufacturing enterprises in Malaysia : Leveraging HRM practices, ICT usage, employee - Ponmalar, Buddatti Sannagy (2024)
Employee performance is becoming increasingly important in optimizing productivity and achieving business goals, including in the manufacturing sector in Malaysia. This study investigates the relationship between human resource (HR) practices (training and development, performance appraisal fairness and mentoring), information and communication technology (ICT) usage, and employee performance in medium manufacturing enterprises (MMEs). The mediating effect of employee engagement and knowledge sharing is also investigated. A total of 301 selfadministered questionnaires were distributed to employees of MMEs in Malaysia. Data was analyzed using partial least squares-structural equation modelling (PLSSEM) approach. The results show that HR practices (training and development, performance appraisal fairness, and mentoring) and ICT usage have a positive and significant impact on employee performance in MMEs. Investing in HRM practices specifically designed for MMEs in Malaysia makes it possible to improve employee performance and increase the success of these companies. Furthermore, employee engagement mediates the relationship between HR practices and employee performance, while knowledge sharing mediates the relationship between ICT usage and employee performance in MMEs. Employee engagement and knowledge sharing are essential factors that contribute significantly in improving employees' performance and productivity alongside HR practices. The study's findings have important practical implications for MMEs. It highlights the crucial role of employee engagement in HR practices and employee performance. MMEs should also encourage greater ICT usage to support knowledge sharing. The proposed research framework draws on social exchange theory to effectively leverage HRM practices, ICT usage, employee engagement, and knowledge sharing. It helps to understand the key factors that impact employee performance in the specific context of MMEs in Malaysia